Penerapan Model Jigsaw Dalam Pembelajaran Keterampilan Membaca Pemahaman Siswa Kelas V SD Kristen Kaiwatu Kabupaten Maluku Barat Daya: Indonesia - Imea, Maria Watmeya; Ririhena, Ribka L.; Sahetapy, Sarah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the improvement in students' reading comprehension skills using the Jigsaw learning model in fifth-grade students of Kaiwatu Christian Elementary School. This study is a classroom action research conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. Each cycle focuses on reading comprehension skills. Prior to implementing the first cycle, the researcher first established communication with the principal and class teachers to conduct research on the application of the Jigsaw learning model in teaching reading comprehension skills to fifth-grade students of Kaiwatu Christian Elementary School, Southwest Maluku Regency. A pre-test was also conducted to determine the students' initial abilities